The effect of prime emulsion components as a function of equilibrium headspace concentration of soursop flavor compounds - Cheong, Kok Whye; Tan, Chin Ping; Mirhosseini, Hamed; Yee, Joanne Kam Wai; Sheikh Abdul Hamid, Nazimah; Osman, Azizah; Basri, Mahiran (Chemistry Central, 2014)
Background Perceptions of food products start when flavor compounds are released from foods, transported and appropriate senses in the oral and nose are triggered. However, the long-term stability of flavor compounds in food product has been a major concern in the food industry due to the complex interactions between key food ingredients (e.g., polysaccharides and proteins). Hence, this study was conducted to formulate emulsion-based beverage using natural food emulsifiers and to understand the interactions between emulsion compositions and flavor compounds. Results The influences of modified starch (x1), whey protein isolate (x2), soursop flavor oil (x3) and deionized water (x4) on the equilibrium headspace concentration of soursop volatile flavor compounds were evaluated using a four-component with constrained extreme vertices mixture design. The results indicated that the equilibrium headspace concentration of soursop flavor compounds were significantly (p < 0.05) influenced by the matrix and structural compositions of the beverage emulsions. Interface formed using modified starch and whey protein isolate (WPI) proved to be capable of inhibiting the release of volatile flavor compounds from the oil to the aqueous phase. Modified starch could retard the overall flavor release through its hydrophobic interactions with volatile flavor compounds and viscosity enhancement effect. Excessive amount of modified starch was also shown to be detrimental to the stability of emulsion system. However, both modified starch and WPI showed to be a much more effective barrier in inhibiting the flavor release of flavor compounds when used as individual emulsifier than as a mixture. Conclusions Overall, the mixture design can be practical in elucidating the complex interactions between key food components and volatile flavor compounds in an emulsion system. These studies will be useful for the manufacturers for the formulation of an optimum beverage emulsion with desirable emulsion properties and desirable flavor release profile.